PENGARUH SENAM HAMIL TERHADAP PENURUNAN TINGKAT NYERI PUNGGUNG BAWAH PADA IBU HAMIL TRIMESTER II DAN III DI PUSKESMAS PARIT RANTANG PAYAKUMBUH TAHUN 2015 - Mera Delima; Maidaliza Maidaliza; Nyki Susanti (JURNAL KESEHATAN PERINTIS, 2015)
Back pain occurs because of changes in hormone levels that increase the pregnancy hormone relaxin, this affects the flexibility of ligamentous tissue that ultimately improve the mobility of the joints in the pelvis and will have an impact on spinal and pelvic instability and cause discomfort. The purpose of this study was to determine the effect pregnancy exercise to decrease lower back pain in pregnant women trimester II and III on the working area of ​​IN Parit Rantang Payakumbuh city in 2015 year. The design of this research is a quasi experimental research. This research had down in Feb 23th 2015 until Mar 9th 2015. The number of samples in This study of 66 people trimester pregnant women II and III. The instrument used for collected data was observation sheet. The result paired t-test intervention group obtained p=0,000 and in the control group=0,107 is no difference in pain reduction in the intervention and control group. The result of independent t-test statistics obtained with 95% degree of confidence that the influence of pregnancy exercise to decrease lower back pain in pregnant women trimester II and III (p = 0.00) with indigo f = 44.755. It is suggested to pregnant women to DAPT doing pregnancy exercise so that lower back pain can be minimized.